Kualifikasi Perundungan sebagai Perbuatan Tindak Pidana - Mumaddadah Mumaddadah; Muammar Muammar (Pusat Riset dan Inovasi Nasional, 2025)
Bullying is a social phenomenon that is increasingly worrying because of its serious impacts on victims, both psychologically, physically, and socially. In the context of Indonesian criminal law, bullying can fulfill the elements of a criminal act if it meets certain qualifications as regulated in the Criminal Code (KUHP) and other regulations. This study aims to analyze how bullying can be qualified as a criminal act and to review the forms of bullying that can be subject to criminal sanctions. Using a normative legal approach, this study examines relevant positive legal norms and case studies that reflect the implementation of the law on bullying. The results of the study show that bullying can be qualified as a criminal act such as insults, physical violence, threats, and defamation, depending on the form and consequences caused. Therefore, it is important to have strict law enforcement and legal education for the community to prevent and handle bullying cases effectively.